Green marketing practices and customer satisfaction: a study of hotels industry in Wennappuwa divisional secretariat. - Perera, H.L.N.; Pushpanathan, A. (Commission on the Geography of Tourism, Leisure and Global Change., 2015)
In the last decade, consumers have become more open-minded on ecological issues. Green marketing refers to selling product or rendering services based on environmental gain. It comes into continuation in late 1980s and early 1990s. Green marketing is rising quickly and consumers are willing to pay a lot for green product. There has been little analysis of the impact of this new market on the consumers and the environment so far. Green marketing affects all areas of our economy, it does not just lead to environmental safety but it also generates new market and job opportunities. Companies that are green stewards stand a chance of gaining many satisfied and loyal customers. Hotel company managers increasingly have to take environmental issues into account. Hotel industry in Sri Lanka has become one of the major income sources to the GNP. With the end of three decades war in Sri Lanka, hotel industry is developing more increasingly. And hotels are developing and implementing different kind of strategies to win the market through enhancing their customer satisfaction. On the other hand customers are now looking for more ecofriendly hotels which secure their health and enhance their satisfaction. The research question of the present study is, how green marketing practices impact on customers satisfactions? Green marketing is a tool for protecting the environment for the future generation. It has a positive impact on environmental safety. Because of the growing concern of environmental protection, there is an emergence of a new market which is the green market. For Hotels to survive in this market, they need to go green in all aspect of their business. Consumers want to identify themselves with hotels that are green compliant and are willing to pay a premium for a greener life style. As such, green marketing is not just an environmental protection tool but also, a marketing strategy. The main objective of the present study is to analysis the relationship between green marketing practices and customer satisfaction. Three hotels in Wennappuwa area were selected for the presents study, such as Club Dolphin Hotel Waikkal, Ranweli Hotel Waikkal and Hotel Heaven Inn. 100 customers selected as sample for the present study. 45 customers were selected from Dolphin Hotel, 35 customers were selected from Ranweli hotel, and 20 customers were selected from Hotel Heaven Inn. The convenience sampling method was used in this study. A structured questionnaire was issued among customers of the hotel industry for collecting data. Environmental product and place strategies were considered as independent variables of the present study and customer satisfaction was considered as dependent variable. SPSS 16 package was used for analyzing the data of the present study. The finding of the present study indicates that the positive relationship was observed among environmental product and place strategies and customer satisfaction of the Hotel Industry in Wennappuwa.
Keywords: Green Marketing Practices; Environmental Product Strategy; Environmental Price Strategy; Customer Satisfaction